2015
DOI: 10.1007/s11442-015-1179-6
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of changes to catchment slope properties in the high-sediment region of the Loess Plateau, 1978–2010

Abstract: Abstract:To control soil erosion and restore the degraded environment in the Loess Plateau, a large number of measures related to soil and water conservation have been employed that have profoundly affected catchment properties. This study constructed three indicators to characterize changes to the catchment slope, proposed both a method for a regression analysis of adjacent images and a sequence model, and applied multisource remotely sensed images and GIS spatial clustering analysis technologies to extract t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…To fully cover the relatively large study area, images for different days were collected and used to address the influence of cloud cover and satellite orbit. To minimize the errors caused by the imaging times of adjacent NDVI images, an adjacent image regression analysis, as described in Zhou et al (2015), was adopted. The accuracy of the resulting VFC for the three periods was assessed using the methodology of Zhou et al (2015) and the result indicated that the overall accuracy was more than 86%.…”
Section: Vfcmentioning
confidence: 99%
See 1 more Smart Citation
“…To fully cover the relatively large study area, images for different days were collected and used to address the influence of cloud cover and satellite orbit. To minimize the errors caused by the imaging times of adjacent NDVI images, an adjacent image regression analysis, as described in Zhou et al (2015), was adopted. The accuracy of the resulting VFC for the three periods was assessed using the methodology of Zhou et al (2015) and the result indicated that the overall accuracy was more than 86%.…”
Section: Vfcmentioning
confidence: 99%
“…To minimize the errors caused by the imaging times of adjacent NDVI images, an adjacent image regression analysis, as described in Zhou et al (2015), was adopted. The accuracy of the resulting VFC for the three periods was assessed using the methodology of Zhou et al (2015) and the result indicated that the overall accuracy was more than 86%. In addition, the accuracy of data obtained for land use and VFC was also identified and accepted at a meeting held by experts from the Yellow River Conservancy Commission of the Ministry of Water Resources at Zhengzhou city in China.…”
Section: Vfcmentioning
confidence: 99%
“…Several studies have analyzed the ET 0 change and the attribution of climate variables to the ET 0 change trend under climate change in South Korea, Slovenia, Egypt, West Africa and China [12][13][14][15][16][17], and different regions showed both increasing or decreasing change trends of ET 0 . Many of these studies only analyzed the ET 0 for historical climatic data and lacked analysis for future periods under climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Rasmussen et al (2012) used the theory of system dynamics to study dynamic trends of land use. However, these methods based on the optimal allocation of single resources may cause negative impacts on the complex overall system of water and land resources, such as the overexploitation of groundwater, a decrease in the quantity of cultivated land or a decrease in soil quality (Li et al 2015;Zhou et al 2015). Therefore, it is necessary to study the joint optimization of the allocation of water and land resources (Tamene et al 2014;Sun et al 2013;Liu et al 2014).…”
Section: Introductionmentioning
confidence: 99%